Women's Quality of Life After Surgical Treatment for Breast Cancer - Daniel Alejandro Arroyo Zumarraga; Ximena Elizabeth Trujillo Romero; Miguel Ramos Argilagos (Revista Finlay)
Foundation: breast cancer requires aggressive treatments such as mastectomy or lumpectomy, followed by radiotherapy or chemotherapy. These procedures can have physical, emotional and social consequences that affect women's quality of life. Objective: to evaluate the level of quality of life and psychosexual functioning of women after surgical treatment for breast cancer. Methods: a descriptive and analytical cross-sectional study was carried out on a sample of 250 women who had undergone surgical treatment for breast cancer. The sample was obtained intentionally according to the selection criteria. The study period was from October 2022 to February 2023. A survey was applied using the instruments: Quality of Life Evaluation Questionnaire or SF-36 in its version 2, Questionnaire for the Measurement of Quality of Sexual Life or scale Mell-Krat, Women's Sexual Functioning Evaluation Questionnaire or SFSI test and the Courtauld Scale of Emotional Control, to evaluate the deviations from the minimum and maximum values of this scale, the Pearson Chi-square test was applied. The data obtained were processed with the STATISTICA software package for statistical analysis and data management. Results: women who underwent mastectomy with breast reconstruction had a better quality of life in terms of physical and psychological functioning compared to those without reconstruction. Women who completed cancer treatment experienced less sexual dysfunction than those still undergoing treatment. Women with higher education, high economic status, and stable employment showed a greater tendency toward more positive health behaviors than those with lower economic and educational status. Conclusions: several factors influence the quality of life and psychosexual functioning of the women studied: the scope of the surgical intervention, the effectiveness of oncological treatment, age, number of children, educational level, economic situation and status labor.